2012
DOI: 10.1128/jcm.01070-11
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis and Identification of Pathogenic Lichtheimia Species by Matrix-Assisted Laser Desorption Ionization–Time of Flight Analyzer-Mediated Mass Spectrometry

Abstract: Zygomycetes of the order Mucorales can cause life-threatening infections in humans. These mucormycoses are emerging and associated with a rapid tissue destruction and high mortality. The resistance of Mucorales to antimycotic substances varies between and within clinically important genera such as Mucor, Rhizopus, and Lichtheimia. Thus, an accurate diagnosis before onset of antimycotic therapy is recommended. Matrix-assisted laser desorption ionization (MALDI)-time of flight (TOF) mass spectrometry (MS) is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 28 publications
(51 reference statements)
2
45
0
1
Order By: Relevance
“…It is also most convenient in the routing laboratory, where solid culture media are mainly used; for instance, nails and hairs suspected to contain dermatophytes are generally incubated on agar plates. Identification by MALDI-TOF MS can, therefore, be carried out immediately from material derived from the original culture, with no additional time-consuming steps described for other protocols (28). The use of this protocol allows also the user to visually identify distinct types of molds growing on the same agar plate, thus avoiding the potential pitfall of liquid cultures that could mask the presence of several organisms.…”
Section: Discussionmentioning
confidence: 99%
“…It is also most convenient in the routing laboratory, where solid culture media are mainly used; for instance, nails and hairs suspected to contain dermatophytes are generally incubated on agar plates. Identification by MALDI-TOF MS can, therefore, be carried out immediately from material derived from the original culture, with no additional time-consuming steps described for other protocols (28). The use of this protocol allows also the user to visually identify distinct types of molds growing on the same agar plate, thus avoiding the potential pitfall of liquid cultures that could mask the presence of several organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of mold isolates for MALDI-TOF MS measurement was done as previously described (14,17). Briefly, 1 ml of fungus-containing medium was transferred to a 1.5-ml Eppendorf tube and centrifuged at 16,000 ϫ g for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to that of bacteria, the cell wall of molds is more robust and rigid, making sample preparation more labor-and time-intensive (13,14). Several studies reported the generation of in-house databases for the Bruker MALDI Biotyper (Bruker Daltonik, Bremen, Germany) covering mainly single genera, such as Aspergillus (15), Fusarium (15,16), Lichtheimia (17), or the Pseudallescheria/Scedosporium complex (18); orders, such as the Mucorales (15); and individual groups of fungi, such as the dermatophytes (19,20) or clinically important molds (14,(21)(22)(23). However, the species coverage of most of these fungus databases is limited, and many are neither publicly nor commercially available.…”
mentioning
confidence: 99%
“…In support of this, the results of antifungal susceptibility testing performed on the isolates from that study indicated that discriminating between Fusarium species complexes may be unnecessary for members of the same species complex (25). (26), which is the second (after Rhizopus) most common causative agent of mucormycosis in Europe. Thus, studies related to Rhizopus species have remained neglected so far, despite the fact that the identification of Rhizopus microsporus and Rhizopus arrhizus (previously known as Rhizopus oryzae), for which the antifungal drug susceptibility profiles are known, may be important for the treatment of mucormycosis.…”
Section: Examples Of Mold Identification By Maldi-tof Msmentioning
confidence: 70%
“…It is worth noting that A. flavus, the second leading cause of human aspergillosis, is not separable from Aspergillus oryzae by means of molecular biology techniques, whereas the closely related species T. mentagrophytes and T. interdigitale are not separable by means of ITS sequence analysis. In contrast, MALDI-TOF MS seems to be more powerful for discrimination between these species (10,32) as well as to distinguish clinically relevant from irrelevant species of Lichtheimia (26). However, as MALDI-TOF MS-based identification should be consistent with the aspect of the organism in culture, relatively mature growth must be achieved before the identification is certain.…”
Section: Mold Identification By Maldi-tof Ms: Is It Really a History mentioning
confidence: 99%